2015
DOI: 10.1007/s00402-014-2147-9
|View full text |Cite
|
Sign up to set email alerts
|

Determining scaphoid waist fracture union by conventional radiographic examination: an analysis of reliability and validity

Abstract: Conventional radiographic imaging is accurate and moderately reliable in diagnosing union, and reliable but inaccurate in diagnosing nonunion of scaphoid waist fractures at 6 weeks follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Therefore, CT scanning is probably the most reliable method of assessing scaphoid union as it can demonstrate trabecular healing crossing the fracture site. 72 This systematic review and meta-analysis show that MRI has the highest sensitivity and specificity for detecting scaphoid fractures. CT and US were shown to be significantly lower.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, CT scanning is probably the most reliable method of assessing scaphoid union as it can demonstrate trabecular healing crossing the fracture site. 72 This systematic review and meta-analysis show that MRI has the highest sensitivity and specificity for detecting scaphoid fractures. CT and US were shown to be significantly lower.…”
Section: Discussionmentioning
confidence: 86%
“…In the early post-trauma period, Dias et al demonstrated that XR cannot be used to identify scaphoid consolidation due to the difficulty of identifying the trabecular crossing of the fracture and sclerosis of the fracture line in the context of the shape and orientation of the scaphoid bone [ 25 , 26 ]. Hannemann suggested that XR at six weeks after injury can be reliably used so as to determine whether scaphoid waist fractures (corresponding to Schernberg’s zones II, III, and IV) have actually healed (k = 0.816 for non-union) [ 27 ]. However, when documenting the union (partially or complete) based on conventional radiographic imaging displays less inter-observer agreement (k = 0.390).…”
Section: Discussionmentioning
confidence: 99%
“…Although Computed Tomography (CT) scans and Magnetic Resonance Imaging (MRI) may provide better evidence of union 33 , 34 , it is not routinely used in our clinical setting. Plain wrist radiographs have been found to be adequate and reliable in diagnosing union postoperatively 31 , 35 , 36 . In addition, our results apply only to open scaphoid fixations with bone grafts and may not necessarily be valid for cases that were performed without bone grafts or performed through minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%